Farmers’ Adaptation Strategies, Coping Behaviour and Barriers to Effective Adaptation to Current Climatic Risks: A Study on Sundarban Region (Indian Journal of Extension Education, 2016)
The Sundarban region is one of the worst climate change hotspots that influences the lives and livelihoods of millions of people. This study was designed to examine the farmers’ coping behaviour, adaptation strategies, and barriers to effective adaptation to current climatic risks. The study was conducted in the Sundarban Region of West Bengal state. Two villages from Kultoli block of South 24 Parganas district were selected. With 40 respondents from each village, total 80 respondents were selected randomly. The main reported adaptation strategies were crop diversification, change in cropping sequence, increase of bund height, diversification of income and livelihood. Farmers have shifted from field crops and fruit orchards to vegetable cultivation. Income from agriculture, fishing and livestock rearing have decreased and people forced to rely more on daily labour.Mainly reported coping strategies were migration, reduction of daily meal in amount and frequency, work as a daily labourand alternate income generating activity. The main barriers for effective adaptation to current climatic risks were lack of resource, lack of knowledge, lack of institutional support, poor extension system and lack of infrastructure.